WOMEN DIRECTORS AND CORPORATE SUSTAINABILITY: BIBLIOMETRIC AND GAP ANALYSIS INSIGHTS - Ananda Febry Mellyanawati; Lulus Kurniasih (Pusat Penelitian dan Pengabdian Masyarakat Sekolah Tinggi Ilmu Ekonomi Trisakti, 2025)
This research explores the connections between gender diversity on corporate boards and corporate sustainability via bibliometric analysis, gap analysis, and a future research agenda. Employing the SPAR-4-SLR based Systematic Literature Review (SLR) protocol, the research examines 43 articles indexed in Scopus that were published from 2014 to 2024. The findings indicate that gender diversity on boards has a positive effect on sustainability performance, especially in the social and governance areas. Main themes encompass stakeholder theory, corporate sustainability, and additional board attributes. Nevertheless, co-authorship analysis reveals restricted cooperation between research teams. The findings emphasize the necessity of varied board compositions for attaining sustainability objectives and aligning with international agendas. Decision-makers are urged to adopt gender diversity programs, whereas business executives ought to cultivate inclusive environments and form sustainability teams. Researchers are encouraged to determine the long-term effects of gender diversity, its relationship with digital transformation, and other aspects of diversity. Upcoming studies should tackle recognized gaps and promote interdisciplinary cooperation to improve comprehension and practices in this area.